Management of diarrheal diseases among children under five years: a case study of mothers at Kakamega county, Kenya - Njeru, Peterson M.; Kariri, John M.; Murigi, Mary W.; Waweru, Heuston M.; Muriithi, Felister M. (International Journal Of Community Medicine And Public Health, 2017)
Background: Despite much effort and successes in the management of diarrhoea, the disease has remained among the top five causes of mortality and morbidity in Kenya, particularly among infants and children below five years. Advent of HIV/AIDS and the harsh economic situation is Kenya has led to increase in diarrhoea diseases. This study was conducted to determine the mother’s knowledge, attitude and practice in the management of diarrheal diseases among children under five years of age. Methods: This was a cross-sectional study conducted at Lurambi sub-County, Kakamega County. Systematic sampling technique was used to determine the study population. The research instruments were; observational checklists, an in-depth interview schedule, self-administered semi-structured questionnaires and focused group discussions. Quantitative data analysis was conducted using SPSSand involved univariate and bivariate analysis. Qualitative data was analyzed by thematic content analysis. Results: Overall, 88% mothers each with at least one child under five years took part in the study. 84% of the respondents had knowledge of the causes of diarrhoea; however only 31% knew methods of diarrhoea prevention. 41% of the respondents managed diarrhoea cases with non-recommended home remedies such as salt and sugar solutions. The study also established that 37% of the health workers were not trained on diarrhoea management despite them being directly involved in the case management. Conclusions: Overall, the research identified a gap between knowledge and practice. There is need for improving home based case management and implementing a community strategy for diarrhoea management.